PENGARUH PERBANDINGAN JUMLAH MEDIA FILTER (Pasir Silika, Karbon Aktif, Zeolit) DALAM KOLOM FILTRASI TERHADAP KUALITAS AIR MINERAL - Suliastuti, Indra; Abrina Anggraini, Sinar Perbawani; Iskandar, Taufik (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Filtration is one of water treatment process that aims to remove suspended solid in water so result purified water. Filtration carried out by seperate solid from water with filter medium. There are many filter medium that use in filtration process, but this study use fine sand, activaited carbon, and zeolit. Filter mediums are series arranged from bottom until the top. The bottom is zeolit, then activated carbon, and the top is fine sand. Water flow through on the top (fine sand), and out from bottom (zeolit). This study aims to find out amount of filter medium effect. Trial done by change amount of filter medium (fine sand, activated carbon, zeolit). The result showed that increase amount of fine sand (from 100 gr to 1500 gr) can reduced concentration of suspended solid. But increase amount of activated carbon (from 100 gr to 1500 gr) is not affected with water physical quality. Zeolit is increased from 100 gr to 1500 gr can be colorless water and reduced turbidity. Kata kunci : Filtration, fine sand, actived carbon, zeolit.